2012
DOI: 10.1002/cjoc.201100657
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Synthesis of the Functionalized Spiro[indoline‐3,4′‐pyridine] via Four‐component Reaction

Abstract: An efficient synthetic procedure for the functionalized spiro[indoline-3,4'-pyridine] was developed via the four-component reactions of arylamines, acetylenedicarboxylates, isatins and malononitrile with triethylamine as the base catalyst. The advantages of this reaction are using common starting material, mild reaction conditions, broad scope of reactants and operational simplicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 30 publications
2
11
0
1
Order By: Relevance
“…The efficient formation of functionalized spiro[indole-3,4’-pyridines] via the four-component reaction prompted us to study the reaction scope further [25]. Another widely used electron-deficient alkyne reagent, methyl propiolate, was utilized to replace dimethyl acetylenedicarboxylate as one component.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The efficient formation of functionalized spiro[indole-3,4’-pyridines] via the four-component reaction prompted us to study the reaction scope further [25]. Another widely used electron-deficient alkyne reagent, methyl propiolate, was utilized to replace dimethyl acetylenedicarboxylate as one component.…”
Section: Resultsmentioning
confidence: 99%
“…General procedure for the synthesis of spiro[indoline-3,4’-pyridine] derivatives 1a–1p : In an analogous manner to our procedure published in [25], a solution of arylamine (2.0 mmol), methyl propiolate (2.0 mmol) in 5 mL ethanol was stirred at room temperature overnight. Then isatin (2.0 mmol), malononitrile (2.0 mmol) and triethylamine (0.4 mmol) were added.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] In the past few years, we have also developed several practical procedures for the synthesis of diverse spirooxindoles via multicomponent reactions by using isatins and its 3-methylene, 3-imino derivatives as the substrates. [28][29][30][31][32][33][34][35][36][37][38][39][40] Recently, we successfully found that spiro[indoline-3,1'-quinolizin]-2-ones, which were generated from the three-component reaction of substituted pyridine, acetylenedicarboxylate and 3-phenacylideneoxindoles, could undergo Diels-Alder reaction with the typical dienophiles such as maleic anhydride and N-phenylmaleimides. [41][42][43] Alternatively, spiro[3H-indole-3,2'-[2H,9aH-pyrido [2,1-b] [1,3]oxazine], which were formed from three-component reaction of the substituted pyridines, electron-deficient alkynes and isatins, also underwent Diels-Alder reaction with 3-phenacylideneoxindoles (eq.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] A number of domino and multicomponent reactions have been developed by using β-enaminones and β-enamino esters to react further with sequential adding nucleophilic or electrophilic reagents to give versatile heterocyclic systems. [11][12][13][14][15][16][17][18][19][20] Against this background and also in the context of our investigations to develop new domino reactions, herein we report the diastereoselective synthesis of functionalized tetrahydropyrimidin-2-thiones via ZnCl 2 promoted one-pot reactions of cyclic amine, methyl propiolate, aromatic aldehydes and thiourea. [11][12][13][14][15][16][17][18][19][20] Against this background and also in the context of our investigations to develop new domino reactions, herein we report the diastereoselective synthesis of functionalized tetrahydropyrimidin-2-thiones via ZnCl 2 promoted one-pot reactions of cyclic amine, methyl propiolate, aromatic aldehydes and thiourea.…”
Section: Introductionmentioning
confidence: 99%